State and prospects of basic computer training in engineering education - O. G. Arkhipov (Открытое образование (Москва), 2016)
Basic computer training is an important part of the fundamental training for engineers in each application area. The article shows that the purpose of such training has been always the formation of the basic theoretical concepts and practical skills to solve problems by programming with computers.All the formation periods and the following improvement of basic computer training were analyzed by the example of the National Research University «Moscow Power Engineering Institute» (NRU MPEI). Special role of the structured programming technology is mentioned, the use of which allows you to effectively develop easy understood algorithms and computer programs with a minimal number of errors.Particular attention is drawn to the serious methodological support in the 80th (the last century), the basic computer training of students by the Ministry of Higher Education of the USSR and the Research Institute of Higher School Problems. The important role of methodical councils of universities on the computer technology application to coordinate in those years the basic computer training at the University is mentioned. The article shows the new teaching methods of the main discipline with generally accepted today in Russia term “Informatics”. This method was developed in the National Research University «Moscow Power Engineering Institute» at the Applied Mathematics Department, providing the basic computer training of students in 1–2 semesters. This new teaching method has such a «reference point» as fundamental programming concepts «task – method of this task solution – algorithm for solving the task – computer program».The main tasks of the discipline of the basic computer training were defined:– formation of students’ formal logic, algorithmic thinking;– learning of modern technology of structured programming, providing efficient development of algorithms and computer programs;– formation of practical skills of designing algorithms of any complexity;– learning of procedure-oriented programming languages.The article analyzes some negative aspects, related to basic computer training and appeared in the last 15–20 years in the National Research University «Moscow Power Engineering Institute» and other higher technical educational universities of Russia, including:– subjective diluting effect, changing the purpose and content of basic computer training and replacement by the other, «unconvincing» in the content subjects;– lack of a unified program of discipline «Informatics» for higher technical educational institutions of Russia;– lack of understanding of the specificity of very intensive work of lecturers, conducting such training, and the underestimation of their labor;– insufficient current level of initial computer training for the secondary school graduates;– lack of methodological interaction of higher technical educational universities of Russia among themselves and with the secondary school on basic computer training.The article emphasizes that the basic computer training in engineering education in Russia will be in perspective realized in its classic historical sense of the word, if the qualified engineers, who are able to think logically and resolve efficiently any professional tasks, will be necessary for the country as before.